Estimated societal costs of stroke in the UK based on a discrete event simulation - Patel, Anita; Berdunov, Vladislav; Quayyum, Zahidul; King, Derek; Knapp, Martin; Wittenberg, Raphael (Oxford Academic, 2022)
This article was published in Age and Ageing [ © The Author(s) 2019. Published by Oxford University Press on behalf of the British Geriatrics Society. This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0/)] and the definite version is available at: https://doi.org/10.1093/ageing/afz162. The Journal's website is at: https://academic.oup.com/ageing/article/49/2/270/5679684?login=true